A potent halogen-bonding donor motif for anion recognition and anion template mechanical bond synthesis - Bunchuay, T; Docker, A; Martinez-Martinez, AJ; Beer, PD (Wiley, 2019)
The covalent attachment of electron deficient perfluoroaryl substituents to a bis-iodotriazole pyridinium group produces a remarkably potent halogen bonding donor motif for anion recognition in aqueous media. Such a motif also establishes halogen bonding anion templation as a highly efficient method for constructing a mechanically interlocked molecule in unprecedented near quantitative yield. The resulting bis-perfluoroaryl substituted iodotriazole pyridinium axle containing halogen bonding [2]rotaxane host exhibits exceptionally strong halide binding affinities in competitive 50 % water containing aqueous media, by a factor of at least three orders of magnitude greater in comparison to a hydrogen bonding rotaxane host analogue. These observations further champion and advance halogen bonding as a powerful tool for recognizing anions in aqueous media.